A Preparatory Study to Validate the Effectiveness of Open and Closed Strategies: An Analysis of Patent Citation Networks of Structural Adhesives - Takefumi MOKUDAI (AAOS Transactions)
This study conducts preparatory work to verify the effectiveness of the “open and closed strategy” for capturing value from innovations. Structural adhesives, which are increasingly being introduced in automotive production, are selected as the subject. Patent data from 1990 to 2019 is used to analyze trends in technological development. An analysis of patent citation networks revealed the following. First, the number of patent applications for structural adhesives in the automotive sector has increased rapidly since the beginning of the 2000s, with European and US adhesive manufacturers, in particular, dominating over the entire period. Second, the density of the citation network is low and divided into a number of clusters, suggesting that segregation by specific technical themes has occurred. Third, backward and forward citations are highly asymmetrical. There are a small number of patents with a vast number of forward citations, while the majority of patents have no citations. Further research is needed to develop criteria and indicators that distinguish closed and open strategies, to examine the relationship between the type of intellectual property strategy, industrial context, and management outcomes, and to explore the source of technological capabilities of firms with strong patent citation networks.